2018
DOI: 10.2147/idr.s153499
|View full text |Cite
|
Sign up to set email alerts
|

Sputum bacteriology conversion and treatment outcome of patients with multidrug-resistant tuberculosis

Abstract: PurposeMultidrug-resistant tuberculosis (MDR-TB) requires long-term treatment, has a high fatality rate, and constitutes a global threat. Earlier detection of treatment failure is required to predict therapeutic efficacy.Patients and methodsWe enrolled MDR-TB patients consecutively from January 2011 through December 2012 in Lianyungang, China. Sputum smear microscopy tests and sputum cultures were performed once a month for the first 6 months following initiation of antituberculosis treatment and once every 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
4
23
2
Order By: Relevance
“…The four-month conversion rate is higher than the study conducted in Latvia (60%). 28 The two-month culture conversion rate in this study was 46.9% which is much lower than the study conducted in Seoul (90.1%) 42 China (65.2%) 47 and Germany (61%), 43 but higher than reported finding from Chinese study (33.3%). 38 The difference in the culture conversion rate among different study sites might be related to a difference in treatment protocol followed in different sites, the difference in the study population, type of drug resistance, and the difference in the quality of reported data.…”
Section: Discussioncontrasting
confidence: 74%
“…The four-month conversion rate is higher than the study conducted in Latvia (60%). 28 The two-month culture conversion rate in this study was 46.9% which is much lower than the study conducted in Seoul (90.1%) 42 China (65.2%) 47 and Germany (61%), 43 but higher than reported finding from Chinese study (33.3%). 38 The difference in the culture conversion rate among different study sites might be related to a difference in treatment protocol followed in different sites, the difference in the study population, type of drug resistance, and the difference in the quality of reported data.…”
Section: Discussioncontrasting
confidence: 74%
“…The high SCC rate was concordant with the treatment success rate among participants in this study, which was the highest ever reported in a domestic study (20)(21)(22) and relatively high globally (6,(23)(24)(25)). This, combined with the declining drug resistance rates among pulmonary tuberculosis patients during 2011-2015 in Hangzhou, e.g.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, this was the highest treatment success rate of MDR-TB patients to be reported in mainland China. [ 19 22 , 25 , 26 ] This marks Hangzhou as the first Chinese city to achieve the WHO target of 75% treatment success. [ 27 ] Treatment success rates reported in other Chinese cities were all under 70%, [ 19 21 , 25 , 26 , 28 , 29 ] and the cure rate ranged from 50% to 60%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 22 , 25 , 26 ] This marks Hangzhou as the first Chinese city to achieve the WHO target of 75% treatment success. [ 27 ] Treatment success rates reported in other Chinese cities were all under 70%, [ 19 21 , 25 , 26 , 28 , 29 ] and the cure rate ranged from 50% to 60%. [ 30 , 31 ] Our study reaffirms a previous study that showed Hangzhou as having a higher MDR-TB treatment success rate (73.7%) than other areas of China.…”
Section: Discussionmentioning
confidence: 99%